Online Learning amid the COVID-19 Pandemic: A Case Study of the State Islamic University of Mataram - Azhar, Azhar (Nadwa: Jurnal Pendidikan Islam, 2020)
This research aims to investigate the challenges and opportunities of the use of information technology in an online learning at the State Islamic University of Mataram (UIN Mataram) during the COVID-19 pandemic. This research incorporates a survey to identify the use of information technology among students. The sample used in this research was the first semester students of the State Islamic University of Mataram (UIN Mataram). The research results indicate that 27.3% of students did not have laptops, 61.8% of students experienced difficulties accessing the telecommunication signal in their home town, and 10.9% experienced electricity problems during online learning. The use of Google Classroom and WhatsApp group media is prevalent at the university during the 2020 COVID-19 pandemic.